The Rights of Access to Justice: UNDP’s Approach and Vietnamese Perspective - Trần, Thị Ánh Hồng (2021)
The thesis explores the provisions of international law on ensuring the right to access justice—also, the thesis analysis measures to ensure the rights to access to justice in UDDP's approach. At the same time, the thesis also presents and evaluates the perspective of approaching justice in Vietnam.Through researching the topic, the author of the thesis will offer several solutions and proposals to improve the effectiveness of the implementation of measures to ensure the right to access justice in Vietnam effectively.